Learning Buddhist Pancasila material on the emotional intelligence of Buddhist students at Gangga junior high school 1 - Mita Mita; Wistina Seneru; Juni Suryanadi (International Journal of Science and Applied Science: Conference Series, 2025)
Buddhist Pancasila is the five basic moral principles in Buddhism that teach self-control and right behaviour, which play an important role in the formation of emotional and spiritual intelligence. Buddhist religious education that instils Buddhist Pancasila values can enhance students' emotional intelligence, helping them to manage their emotions and behave positively in society. The purpose of this study was to examine the effect of teaching Buddhist Pancasila material on the emotional intelligence of Buddhist students at Gangga Junior High School 1. This study uses a quantitative approach, using. To determine the sample size in each class, a professional allocation of 7 samples was used, consisting of 26 seventh-grade students, 38 eighth-grade students, and 23 ninth-grade students. This study was conducted at Gangga Junior High School 1 with respondents from seventh, eighth, and eleventh grades who are Buddhist, in the 2024/2025 academic year. The results of this study show that there is a positive and significant effect of Buddhist Pancasila education on students' emotional intelligence, with a calculated t-value of (p). From these results, it can be interpreted that Buddhist Pancasila education has a positive effect on emotional intelligence. The magnitude of the effect can be seen from the results of a simple linear test, which found an r square value of, meaning that Buddhist Pancasila education has an effect on emotional intelligence.